2020
DOI: 10.1016/j.jid.2019.06.149
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Melanoma by TERT Promoter Mutational Status

Abstract: Although TERT promoter mutations have been associated with a worsened prognosis in melanoma, the relationship between mutation status and downstream telomerase activity and telomere length remains convoluted. Using Sanger sequencing and techniques based on quantitative reverse transcriptase in real time, we evaluated 60 melanoma cell lines for TERT promoter mutational status, copy number, gene expression, and telomere length to provide a comprehensive analysis of the TERT/telomere pathway and establish a class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 16 publications
(16 reference statements)
0
30
0
Order By: Relevance
“…When we investigated the role of the rs2853669 polymorphism at −245 bp, which reportedly counteracts the activating effect of the above-mentioned TERTprom mutations [25] and modulates their negative effect on melanoma survival [4], we found that the SNP did not interfere with the effect of the two hotspots on treatment outcome and was not associated with telomere length, as opposed to what was observed in melanoma cell lines [26].…”
Section: Discussionmentioning
confidence: 90%
“…When we investigated the role of the rs2853669 polymorphism at −245 bp, which reportedly counteracts the activating effect of the above-mentioned TERTprom mutations [25] and modulates their negative effect on melanoma survival [4], we found that the SNP did not interfere with the effect of the two hotspots on treatment outcome and was not associated with telomere length, as opposed to what was observed in melanoma cell lines [26].…”
Section: Discussionmentioning
confidence: 90%
“…Many of the identified noncoding hotspots were located in sequences of genes functionally related to cancer or more specifically to UV radiation-related skin cancers. Some of them were reported before in melanoma or identified by us in melanoma TCGA samples, the cancer type most intensively studied in terms of mutations in noncoding regions [109,110]. Below, we briefly describe the cancer-related role of the three most interesting genes with hotspot mutations in noncoding regions, i.e., BAD , DHODH , and CHCHD2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that TERT mutations could lead to overexpression of TERT in several cancers. For example, transcriptional activity of TERT with c.-124C > T, c.-146C > T or c.-57A > C was higher than wild type in melanoma [23,30]; Cao et al [31] reported that ampli cation of TERT increase the expression of TERT; Bayard et al [32] reported that rearrangement of TERT could induce overexpression of TERT. In survival analysis, we found that TERT mutations correlated with shorter TTP and OS of HCC patients underwent hepatectomy.…”
Section: Discussionmentioning
confidence: 99%